2018
DOI: 10.2741/e837
|View full text |Cite
|
Sign up to set email alerts
|

MHC-B haplotypes impact susceptibility and resistance to RSV-A infection

Abstract: We investigated the impact of haplotype of major histocompatibility complex (MHC)-B on the outcome of infection of Synthetic Dam Line (SDL) broiler strain with Rous Sarcoma Virus (RSV). Genomic analysis of MHC-B haplotypes, revealed a total of 12 known standard haplotypes that constituted to twenty-five different genotypes and one new haplotype of 217 bp size, designated B. The inoculation of RSV-A in SDL chicks resulted in the development of tumors of progressive or regressive phenotypes with varying tumor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…But anchor residue motifs of B have not been studied yet. This result is basically coincident with the findings of Vishwa et al 9 (B21 has less mortality and was resistant to RSV‐A tumor, while B15 susceptibility to RSV‐A tumor) and Hunt et al 10 (B21 has less mortality and was resistant to H5N1 viruses). They concluded that this miscellaneous binding furthers our grasp of modes that BF can present peptides to the T lymphocytes and may account for the resistance of the B21 haplotype to MD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…But anchor residue motifs of B have not been studied yet. This result is basically coincident with the findings of Vishwa et al 9 (B21 has less mortality and was resistant to RSV‐A tumor, while B15 susceptibility to RSV‐A tumor) and Hunt et al 10 (B21 has less mortality and was resistant to H5N1 viruses). They concluded that this miscellaneous binding furthers our grasp of modes that BF can present peptides to the T lymphocytes and may account for the resistance of the B21 haplotype to MD.…”
Section: Discussionsupporting
confidence: 90%
“…Resistance to lymphomas originating from pathogenic microorganisms, 8 such as MDV and/or RSV 9 and/or avian influenza viruses, 10 has a close connection with the BF in the chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detection of ANA or abnormal cryoglobulins might be explained by an altered function of suppressor T cells and by proliferation of monoclonal B lymphoid cells ( 19 , 20 ). Finally, diversity of the major histocompatibility complex and innate immune gene expression have a significant positive correlation with resistance or susceptibility to various types of cancers ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Proteins are represented in different forms such as receptors, enzymes, ion channels, transporters, regulatory proteins (Alexander et al, 2019a;Alexander et al, 2019b;Alexander et al, 2019c;Alexander et al, 2019d;Alexander et al, 2019e;Alexander et al, 2019f;Alexander et al, 2019g), cytokines, chemokines (Khare et al, 2019), structural proteins, cytoskeletal proteins, microtubules forming the mitotic spindle, transcription factors, and hormones. MHC-B complex genes that encode for cell surface proteins, are activated and affect the tumor outcome (Khare et al, 2018). It has been reported that most SM apparently interact with proteins and change the protein conformation in an unselective manner (binding, complexing, and denaturing).…”
Section: Major Cellular Targets For Secondary Metabolitesmentioning
confidence: 99%